The siren eaudiobook - Cass, Kiera (2016)
#1 New York Times bestseller A sweeping stand-alone fantasy romance from Kiera Cass, author of the beloved, bestselling Selection series. Kahlen is a Siren—bound to serve the Ocean by luring humans to their watery graves with her voice, which is deadly to any human who hears it. Akinli is human—a kind, handsome boy who's everything Kahlen ever dreamed of. Falling in love puts them both in danger... but will Kahlen risk everything to follow her heart? This star-crossed YA romance is sure to captivate readers who grew up loving The Little Mermaid or fans of Jennifer Donnelly's Waterfire Saga. Originally self-published, The Siren has been completely rewritten for this edition. Don't miss The Betrothed, a glittering royal romance sure to captivate Kiera Cass's legion of loyal readers and lovers of courtly intrigue alike!